2004
DOI: 10.1507/endocrj.51.333
|View full text |Cite
|
Sign up to set email alerts
|

JunD-Menin Interaction Regulates c-Jun-mediated AP-1 Transactivation

Abstract: Abstract. The gene responsible for multiple endocrine neoplasia type 1, MEN1, encodes the 610-amino acid-protein, menin. Although menin has been reported to bind AP-1 transcription factor JunD and suppress its transcriptional activity, little is known about its molecular mechanisms and physiological role. To better understand the function of menin and its significance in tumorigenesis, we investigated the effect of wild-type and mutant menin proteins on AP-1 transactivation. In COS cells, wild-type menin suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Pin1 and Men1 are involved in regulating the magnitude host signaling networks including AP-1, while MAGEA11 regulates HIF1α activity (Aprelikova et al, 2009; Ikeo et al, 2004; Lee et al, 2009; Monje et al, 2005). Both cellular functions have been implicated as important during C. trachomatis infection, and we wanted to confirm their role.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pin1 and Men1 are involved in regulating the magnitude host signaling networks including AP-1, while MAGEA11 regulates HIF1α activity (Aprelikova et al, 2009; Ikeo et al, 2004; Lee et al, 2009; Monje et al, 2005). Both cellular functions have been implicated as important during C. trachomatis infection, and we wanted to confirm their role.…”
Section: Resultsmentioning
confidence: 99%
“…When we individually examined the role of the 13 genes identified in the loss-of-function screen using natural language processing we also found several genes, including Pin1 and Men1, that directly influence the activation and amplitude of the host transcription factor AP-1 (Chen et al, 2009; Chittenden et al, 2008; Ikeo et al, 2004; Park et al, 2012)(Figure S3). AP-1 is a heterodimeric transcription factor usually made up of a Jun and Fos protein that together regulate the expression of a large range of host genes related to inflammation, stress, and cell survival (Schonthaler et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…However, it has recently been shown that JunD, in the absence of menin, switches from a growth suppressor to a growth promoter (Agarwal et al 2003). Conversely, menin, in the absence of JunD, stimulates the transcriptional activity of c-Jun, a growth promoter protein (Ikeo et al 2004). These results suggest that JunD and menin generally function in combination when they exert their biological effects in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The gene product, menin, is a nuclear protein that interacts with several proteins involved in transcriptional regulation, genome stability, and cell proliferation. It has been demonstrated to bind JunD and suppress its activity and also to enhance the activity of c-Jun , Ikeo et al 2004, but the precise mechanism for menin's role as a tumor suppressor still remains unclear.…”
Section: Multiple Endocrine Neoplasia Typementioning
confidence: 99%
“…However, the model does not provide an explanation for the two distinct transcription profiles seen in these tumors. Augmentation of c-Jun activity induced by menin , Ikeo et al 2004) and blocking of c-Jun upregulation by MYC (Vaque et al 2008) may suggest potential roles for MEN1 and MAX mutations in this context, although it remains to be investigated. Karasek et al (2010) for definitions) and immunohistochemical staining for SDHB (perhaps in combination with SDHA) can, when available, be used as a complement guide to what genes should be prioritized.…”
Section: Developmental Apoptosis Of Neuronal Precursor Cellsmentioning
confidence: 99%